AN ASSESSMENT OF EMERGENCY FIRE DISASTER PREPAREDNESS IN PUBLICAND PRIVATE SECONDARY SCHOOLS IN KENYA: A COMPARATIVE STUDY - Paul Okeyo Ogembo (CV. ADIBA AISHA AMIRA, 2025)
Fire emergency is a common phenomenon in educational institutions, usually with lethal results if not immediately in an event of outbreak. The consequences usually include loss of life, injuries, destruction of property and institutional facilities in this year alone nearly 50 cases of school fire outbreaks have been reported in Kenya with disastrous results. Yet a comparative study of this nature in the named country is hardly there and hence it will bridge the knowledge gap in the concern. The purpose of the study was to assess the emergency of fire disaster preparedness in public and private secondary schools in Kenya.Spefically the study sought to determine the causes of frequent fire outbreaks in educational institutions in Kenya; to determine the consequences of fire outbreaks in Kenyan schools; determine the fire emergency preparedness in schools within the framework established by the Ministry of Education 2008 and to determine the way forward toward fire emergency preparedness in Kenyan Secondary schools. The study adopted meta-analysis of empirical studies in accordance to Ferrer 1998.The study established that: there are diverse causes of fire outbreaks in schools including electric faults, eruption of gas cylinders in the laboratories, use of candles in the dormitories in case of blackouts, students’ misunderstandings with school administration leading to strikes and burning schools’ property, others could be due to suspicious arsonist work. Consequences of fire outbreaks include destruction of schools’ infrastructure and property and students’ belongings, injuries and even death. That most of schools do not meet the required MOEST schools’ safety standards (2008), with grilled windows, lack of fire extinguishers, no fire assembly site. That way forward includes meeting MOEST safety guidelines, schools’ finding means preventing any possible strikes that can lead to burning of schools’ property.